Peran Murabahah Dalam Mendukung Usaha Mikro Kecil Dan Menengah: Tinjauan Dari Sudut Pandang Bank Syariah - Lismawati, Lismawati; Winario, Mohd; Khairi, Rifqil (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This article evaluates the role of Murabahah in supporting Micro, Small and Medium Enterprises (MSMEs) from the perspective of Islamic banks. Through a literature review, this study highlights that Murabahah provides capital solutions in accordance with sharia principles, facilitating MSMEs' access to working capital and investment. Other benefits include certainty in prices and transparent costs as well as flexibility in the financing period and types of goods that can be financed. The study results show that Murabahah not only provides direct financial benefits, but also increases financial literacy and financial inclusion of MSMEs. With the help of Islamic banks, MSMEs can manage their finances better, increasing their ability to make more precise and sustainable business decisions.